The Development of the Water-Energy-Food Nexus as a Framework for Achieving Resource Security: A Review - Simpson, Gareth B.; Jewitt, Graham P. W. (Frontiers in Environmental Science, 2019)
This paper presents a study of the evolution of the water-energy-food (WEF) nexus since its rise to prominence in policy and development discourses in 2011. The paper presents various interpretations of the concept as well as the novelty the WEF nexus. The challenge of integrating and optimising the components of this multi-centric nexus is examined, with four case studies being presented. Various criticisms levelled at the WEF nexus, such as the neglect of livelihoods and the environment in assessments, are noted, together with governance considerations associated with this framework. Finally, the potential of the WEF nexus to contribute to the achievement of the Sustainable Development Goals is reviewed.